Investigating Students’ Attitudes Toward Writing Assignments Through Social Media E-Portfolio - Riki Ruswandi; Wahyu Satya Gumelar; Rifqi Rayhani (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2024)
As technology progresses rapidly, e-portfolio have been utilized by teachers to hone their students’ language skills. Social media is a viable option as a platform for e-portfolio since it has been a part of people’s daily life and learning. It allows students to compile and share their work publicly and they are accustomed to it. It is a great place to learn writing as well. This research focuses on revealing the utilization of weblog-based social media e-portfolio and investigatInstagramnts’ attitudes toward e-portfolio on social media (Instagram), along with finding out the circumstances behind their attitudes. The participants of this study were the students of XI IPA 1 class of SMA Istiqamah Bandung academic year 2022/2023. They were assigned to a personal letter-writing task and interviewed. This qualitative case study aims to discover the students’ attitudes toward writing assignment portfolios in social media since attitude in language learning yields a deciding factor of whether students are going to get engaged in the process or not. The data were collected through an interview, teacher’s field notes, and the collection of the students’ writings. The data is then analyzed through the organization of data, data exploration and coding, data description, findings report, findings interpretation, and validation. The results indicated that students held positive attitudes toward it although not in every category of each attitude aspect. Students expected improvement and managed to be positively engaged in the learning process.